(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
This article presents methods for assessing the innovative development and compe-titiveness of the industrial sector in the Republic of Bulgaria. Guidelines and recommendations for their acceleration are indicated. A cross-section of the Bulga-rian industry is also made, assessing the innovative acceleration of the technologies used.